Tant qu’il y aura des forêts. Écriture, parentés et résistances écoféministes - Anne Isabelle François (Itinéraires)
This paper examines the ecofeminist issues of interconnection (of both dominations and lives) as well as possibilities of re-appropriation in three contemporary fictions by female writers (Haushofer, Hegland, Darrieussecq) in a comparative perspective. Is it possible to restructure and rethink our experience of the world outside the hegemonic and destructive system that can only lead to a global catastrophe? The texts, read as speculative and pragmatic propositions, allow us to imagine an ecofeminist way of living: the female protagonists write about their survival in the forest, bringing about a liveable future that reconfigures boundaries and allegiances, voicing an intimate experience of co-presence. These narratives of agency and transformation are read through Donna Haraway’s theories: at their core is the acknowledgement of our relations and links, understood as related to issues of kinship, care, the redesigning of alliances, an attention to significant others, outside the alienating capitalocene regime of exploitation. They also look into issues of writing, testimony and transmission. Literature forms a vector to rethink and reposition the human being as a creature of the world, to explore and question the imaginable, thus offering a space to implement (counter-)practices, situated knowledge and ecofeminist ethics and mode of attention.